Development of a “Wevernal” Tourism Village of Selindung Jerambah Gangung as a Tourist Village Through Strengthening Organization And Business Management Based on Local Potential - Devi Valeriani; Dian Prihardini Wibawa; Ayu Wulandari; Herry Marta Saputra (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The 2024 University Level Community Service Program (PMTU) with the title Development of Jerambah Gantung Subdistrict and Selindung Subdistrict as Tourist Villages Through Strengthening Organization and Local Potential Based Business Management, focuses on this Tourism Village object because it is based on an analysis of the potential of Tourism Villages which has been carried out by Bappeda Pangkalpinang City has determined that these two sub-districts are designated as Tourism Villages which are alternative tourism for tourists visiting Pangkalpinang City. In establishing these two sub-districts as tourist villages, it is necessary to optimize business actors in the souvenir, culinary, home stay and souvenir industries, bearing in mind that every tourist when traveling will almost certainly shop for souvenirs and souvenirs, enjoy culinary delights and stay overnight in homestay. For this reason, it is necessary to strengthen business organization and management so that Jerambah Gantung Village and Selindung Village are ready to become tourist villages in Pangkalpinang City. The aim is to create the development of a Tourism Village through participatory planning so as to create organizational and business management strengthening based on local potential, for business actors. The methods used are training, mentoring and implementation. Meanwhile, the cooperation partners in carrying out this service are the village governments of Jerambah Gantung Subdistrict and Selindung Subdistrict, including the Pangkalpinang City Tourism Office.